MULTIKULTURALISME DALAM ALQURAN - Siregar, Idris (BASHA'IR: JURNAL STUDI AL-QUR'AN DAN TAFSIR, 2022)
This study aims to find out how multiculturalism is in the perspective of the Koran, what is the opinion of the mufassir regarding the verses of multiculturalism. And how multiculturalism affects the substance of the season. This research is library research. By collecting data related to this research, then described based on the data obtained and analyzed. The data collection technique used is by collecting books, books and articles related to this title. There are three things that are the results of this research, First, that the Qur'an supports the concept of multiculturalism, because the Qur'an also talks about tribes and nations (Q.S. Al-Hujurat/48: 13), Allah swt., also makes humans not in one people (types of people). ) only (Q.S. Al-Maidah/5: 48), and the Qur'an commands Muhammad, peace be upon him, to be kind to all mankind (Muslim non-Muslims) (Q.S. Al-Anbiyā'21: 107). Second, the opinion of the commentators regarding the verses of multiculturalism is, indirectly that they believe in multiculturalism in the Qur'an, such as Abū Ja'far aṭ-Ṭabarī (d. 310 H) and Ibn Kathir (d. 774 H) interpret the word sawa' by treating anyone fairly regardless of the subject, whether he is Muslim or non-Muslim. Third, the indicators for the multiculturalism verse are, if found in the Qur'an, words that are (a) global interjections, such as 'yā ayyuhā an-nās', (b) equality/justice words, such as 'sawā', (c) ummah, such as 'ummatun.